MRI guided focused ultrasound robotic system for the treatment of gynaecological tumors - Epaminonda, Eva; Drakos, Theoharis; Kalogirou, Christina; Theodoulou, Margarita; Yiallouras, Christos; Damianou, Christakis A. (My University, 2016)
Background: A novel MRI-conditional robot that navigates focused ultrasound (FUS) for the treatment of gynaecological tumors endovaginally was developed. Methods: The robotic system has two PC-controlled axes (linear and angular). The robotic system was manufactured using a digital manufacturing 3D printer using acrylonitrile butadiene styrene (ABS) plastic. Evaluation of the device was performed in a 1.5T MRI using excised porcine tissue. Results: The robotic system was successfully tested for MRI safety and compatibility. The robotic system has been tested for its functionality for creating multiple (overlapping) lesions in an in vitro model. Conclusions: An MRI-conditional FUS robotic system was developed that has the potential to create thermal lesions with the intention of treating gynaecological tumors. In the future a third axis will be needed that lifts the robot up or down in order to access vaginas which are at a variable height from the MRI table.
Keywords: MRI; Gynaecological; Robot